Chlamydia Trachomatis Secretion of Proteases for Manipulating Host Signaling Pathways - Zhong, Guangming (Frontiers in Microbiology, 2011)
The human pathogen Chlamydia trachomatis secretes numerous effectors into host cells in order to successfully establish and complete the intracellular growth cycle. Three C. trachomatis proteases [chlamydial proteasome/protease-like activity factor (CPAF), tail-specific protease (Tsp), and chlamydial high temperature requirement protein A (cHtrA)] have been localized in the cytosol of the infected cells either by direct immunofluorescence visualization or functional implication. Both CPAF and Tsp have been found to play important roles in C. trachomatis interactions with host cells although the cellular targets of cHtrA have not been identified. All three proteases contain a putative N-terminal signal sequence, suggesting that they may be secreted via a sec-dependent pathway. However, these proteases are also found in chlamydial organism-free vesicles in the lumen of the chlamydial inclusions before they are secreted into host cell cytosol, suggesting that these proteases may first be translocated into the periplasmic region via a sec-dependent pathway and then exported outside of the organisms via an outer membrane vesicles (OMVs) budding mechanism. The vesiculized proteases in the inclusion lumen can finally enter host cell cytosol via vesicle fusing with or passing through the inclusion membrane. Continuing identification and characterization of the C. trachomatis-secreted proteins (CtSPs) will not only promote our understanding of C. trachomatis pathogenic mechanisms but also allow us to gain novel insights into the OMV pathway, a well-known mechanism used by bacteria to export virulence factors although its mechanism remains elusive.